2005
DOI: 10.1177/039463200501800407
|View full text |Cite
|
Sign up to set email alerts
|

Iron Availability Influences Aggregation, Biofilm, Adhesion and Invasion of Pseudomonas Aeruginosa and Burkholderia Cenocepacia

Abstract: Pseudomonas aeruginosa and Burkholderia cenocepacia are predominant opportunistic pathogens in cystic fibrosis (CF) patients. In healthy humans the lower respiratory tract as well as all mucosa, contains a very low free iron concentration (10-18 M), while in CF patients' sputum iron concentration is very high, showing a median value of 63x10-6 M. Accumulation of catalytic reactive iron heavily contributes to subsequent clinical complications in the lung disorders by the production of reactive oxygen species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 29 publications
5
96
1
1
Order By: Relevance
“…Twitching is a specialized type of motility of bacteria that wander across the colonized surface instead of forming biofilm (2). Similar results were also reported for Burkholderia cenocepacia where motility inversely correlates with iron availability (3). Moreover, iron highly influences the morphological forms 'of both p. aeruginosa and B. cenocepacia, since different levels of iron availability induces bacteria to form aggregates or biofilm (3).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Twitching is a specialized type of motility of bacteria that wander across the colonized surface instead of forming biofilm (2). Similar results were also reported for Burkholderia cenocepacia where motility inversely correlates with iron availability (3). Moreover, iron highly influences the morphological forms 'of both p. aeruginosa and B. cenocepacia, since different levels of iron availability induces bacteria to form aggregates or biofilm (3).…”
supporting
confidence: 58%
“…biofilm, in the respiratory tract of CF patients (6)(7). Furthermore, the ability of P. aeruginosa and B. cenocepacia to regulate their mode of growth (freeliving, aggregates and biofilm) depending on iron availability confers to these pathogens the chance to modulate their adhesion and invasion efficiency into host cells (3).…”
mentioning
confidence: 99%
“…The link between Fe and biofilm formation (9)(10)(11)(12) and the fact that Ga can disrupt Fe-dependent processes (21) led us to investigate the effect of Ga on P. aeruginosa biofilm development. Studying Ga's effects on biofilms was also of interest because low concentrations of a number of antibiotics promote biofilm formation, perhaps because biofilm growth can be induced as a consequence of stress (22)(23)(24)(25).…”
Section: Figurementioning
confidence: 99%
“…High levels of Fe are required for the formation of cell clusters early in biofilm development and for the maturation of biofilms into 3-dimensional structures (9)(10)(11)(12). Fe-withholding defenses may also be protective during infection, as bacteria taken from infection sites show gene expression profiles of Fe starvation (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…There is a variety of evidence implicating iron acquisition in microbial pathogenesis. Over a decade ago, Berlutti et al (2005) demonstrated that iron availability impacts on biofilm formation, adhesion and invasion of two important CF pathogens, P. aeruginosa and Burkholderia cenocepacia. More recently, Wiens et al (2014) demonstrated that alginate production, mucoid phenotype and biofilm formation by P. aeruginosa are iron regulated.…”
Section: Iron and Cfmentioning
confidence: 99%